Summer stream habitat preferences of Nunavik anadromous Arctic char ( Salvelinus alpinus) fry and parr - Dubos, Véronique; St-Hilaire, André; Bergeron, Normand E. (Canadian Journal of Fisheries and Aquatic Sciences, 2022)
Arctic char (Salvelinus alpinus) is a fish species known to occupy diverse habitats within the Arctic region. However, summer habitat use during the juvenile stage of the anadromous form is largely unknown. The present study aims to characterize fry and parr summer habitat preferences. Surveys were conducted by electrofishing, associated with physical habitat characterization on several rivers of the Ungava Bay, Nunavik, Canada. At the microhabitat and station scales (group of microhabitats), fry showed significant habitat preferences for shallow water and slow velocity. At the mesohabitat scale, fry showed a significant habitat selectivity for riffles. This habitat selectivity implies that habitat models can be built to evaluate the potential of habitat suitability for Arctic char fry. However, no significant habitat selectivity was found for parr. Parr size was nonetheless positively correlated with velocity, which was found to be a limitative factor for juvenile habitat use. This first attempt at modeling juvenile anadromous Arctic char habitat in rivers emphasizes the importance of selecting an appropriate spatial scale and reiterates the fact that parr showed relatively high plasticity in stream habitat selection.